Reduced (15)N Losses by Winter and Spring Night-Warming Are Related to Root Distribution of Winter Wheat - Hu, Chenxi (Front Plant Sci, 2019)
To develop efficient N management strategies for high wheat NUE and minimizing the environmental impact of N losses under asymmetric warming, (15)N micro-plot experiments were conducted to investigate the effects of night-warming during winter (warming by 1.47–1.56°C from tillering to jointing), spring (warming by 1.68–1.82°C from jointing to booting), and winter + spring (warming by 1.53–1.64°C from tillering to booting) on root growth and distribution of winter wheat, the fates of (15)N-labeled fertilizer, and their relationships in 2015–2017. The results showed that night-warming increased the recovery of basal (15)N and top-dressed (15)N, while reduced the residual and loss of basal (15)N and top-dressed (15)N. The losses decreases of top-dressed (15)N were higher than those of basal (15)N, indicating that night-warming reduced losses of fertilizer (15)N mainly by reducing losses of top–dressed (15)N. Moreover, pre-anthesis root dry matter accumulation rate in 0–60 cm soil layer were promoted, resulted in improved root biomass and root/shoot ratio, which favored increasing recovery of fertilizer (15)N and reducing losses of fertilizer (15)N. Furthermore, residual fertilizer (15)N content in 0–100 cm soil layer was reduced, which was associated with improved root weight density in 0–60 cm soil layer, resulted in reduced leaching losses of fertilizer (15)N. The path analysis showed that root dry matter distribution in 0–20 cm soil layer was the most important in contributing to reducing losses of total fertilizer (15)N compared with other soil layers. Two years data showed that winter and spring night-warming gave better root growth and distribution in 0–20 cm soil layer, resulted in reduced the losses of fertilizer (15)N and improved the recovery of fertilizer (15)N, while maximizing grain yield of winter wheat, and winter + spring night-warming resulted in higher advantages than winter night-warming and spring night-warming.